Comparative analysis of shariah review practices between Bank Rakyat and RHB Islamic Bank Berhad - Wan Nurliza binti W. Ramli (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
Shariah review is an essential element of an Islamic Financial institution. It plays the role of ensuring the compliance of banks' business activities and transactions to the Shariah principles. This research seeks to identify the practice of Shariah review in Bank Kerjasama Rakyat Malaysia and RHB Islamic Bank Berhad in reference to Shariah Governance Framework of Bank Negara Malaysia. The ambiguous nature of Shariah Review function explained in the Shariah Governance Framework of Bank Negara Malaysia has caused a number of differences in Shariah review practice between Islamic Financial Institutions in Malaysia. This research will be highlighting the differences which followed by the recommendations on how to close the gaps between these different practices. It is without a doubt that the framework of Bank Negara Malaysia is instrumental to the formation of Shariah Review structures and governance in general. However, the framework is lacking in terms of its comprehensive explanation.